One hundred eighteen taxonomic changes among Xyleborine ambrosia beetles (Coleoptera: Curculionidae: Scolytinae) - Smith, Sarah M.; Beaver, Roger A.; Sittichaya, Wisut; Cognato, Anthony I (Zootaxa, 2022)
An ongoing study of the ambrosia beetle tribe Xyleborini has resulted in numerous taxonomic changes mostly representing new generic/species combinations which remove species from the once all-encompassing Xyleborus Eichhoff, 1864 to other genera based on revised taxonomic concepts. These changes are here listed. Terminalinus Hopkins, 1915 is removed from synonymy with Cyclorhipidion Hagedorn, 1912 and reinstated as a valid genus. Five species are removed from synonymy and reinstated as valid species: Amasa brevipennis (Schedl, 1971), Amasa fulgens (Schedl, 1975), Ambrosiophilus immitatrix (Schedl, 1975), Ambrosiophilus semirufus (Schedl, 1959), Microperus leprosulus (Schedl, 1936). The following 97 new or restored combinations are proposed: Ambrosiophilus bispinosulus (Schedl, 1961) comb. nov., Ambrosiophilus compressus (Lea, 1894) comb. nov., Ambrosiophilus latecompressus (Schedl, 1936) comb. nov., Ambrosiophilus pertortuosus (Schedl, 1942) comb. nov., Ambrosiophilus tomicoides (Eggers, 1923) comb. nov., Ambrosiophilus tortuosus (Schedl, 1942) comb. nov., Euwallacea obliquecauda (Motschulsky, 1863) comb. nov., all from Ambrosiodmus Hopkins, 1915; Coptodryas decepta (Schedl, 1979) comb. nov., Microperus pusillus (Eggers, 1927) comb. nov., both from Arixyleborus Hopkins, 1915; Coptodryas pseudopunctula (Schedl, 1942) comb. nov., from Cnestus Sampson, 1911; Microperus abbreviatus (Schedl, 1942) comb. nov., Microperus amphicauda (Browne, 1986) comb. nov., Microperus borneensis (Browne, 1986) comb. nov., Microperus comptus (Sampson, 1919) comb. nov., Microperus gorontalosus (Schedl, 1939) comb. nov., Microperus pullus (Schedl, 1952) comb. nov., Microperus tenellus (Schedl, 1959) comb. nov., Microperus vafer Schedl, 1957 comb. nov., all from Coptodryas Hopkins, 1915; Ambrosiophilus pityogenes (Schedl, 1936) comb. nov., Arixyleborus scapularis (Schedl, 1942) comb. nov., Beaverium dihingicum (Wood, 1992) comb. nov., Beaverium rufonitidus (Schedl, 1951) comb. nov., Coptodryas brevior (Eggers) comb. nov., Terminalinus dipterocarpi Hopkins, 1915 comb. res., Terminalinus sexspinatus (Schedl, 1935) comb. nov., Terminalinus terminaliae (Hopkins, 1915) comb. res., Truncaudum leverensis (Browne, 1986) comb. nov., all from Cyclorhipidion Hagedorn, 1912; Planiculus kororensis (Wood, 1960) comb. nov., Planiculus loricatus (Schedl, 1933) comb. nov., Planiculus murudensis (Browne, 1965) comb. nov., all from Euwallacea Reitter, 1915; Terminalinus anisopterae (Browne, 1983) comb. nov., Terminalinus indigens (Schedl, 1955) comb. nov., Terminalinus macropterus (Schedl, 1935) comb. nov., Terminalinus major (Stebbing, 1909) comb. nov., Terminalinus pilifer (Eggers, 1923) comb. nov., Terminalinus posticepilosus (Schedl, 1951) comb. res., Terminalinus pseudopilifer (Schedl, 1936) comb. nov., Terminalinus sulcinoides (Schedl, 1974) comb. nov., all from Fortiborus Hulcr & Cognato, 2010; Microperus micrographus (Schedl, 1958) comb. nov., Microperus truncatipennis (Schedl, 1961) comb. nov., both from Xyleborinus Reitter, 1913; Ambrosiophilus immitatrix (Schedl, 1975) comb. nov., Ambrosiophilus semirufus (Schedl, 1959) comb. nov., Arixyleborus crenulatus (Eggers, 1920) comb. nov., Arixyleborus strombosiopsis (Schedl, 1957) comb. nov., Beaverium batoensis (Eggers, 1923) comb. nov., Beaverium calvus (Schedl, 1942) comb. nov., Beaverium obstipus (Schedl, 1935) comb. nov., Beaverium rufus (Schedl, 1951) comb. nov., Coptodryas cuneola (Eggers, 1927) comb. nov., Cyclorhipidion amanicum (Hagedorn, 1910) comb. nov., Cyclorhipidion impar (Eggers, 1927) comb. nov., Cyclorhipidion inaequale (Schedl, 1934) comb. nov., Cyclorhipidion kajangensis (Schedl, 1942) comb. nov., Cyclorhipidion obiensis (Browne, 1980) comb. nov., Cyclorhipidion obtusatum (Schedl, 1972) comb. nov., Cyclorhipidion perpunctatum (Schedl, 1971) comb. nov., Cyclorhipidion repositum (Schedl) comb. nov., Cyclorhipidion separandum (Schedl, 1971) comb. nov., Debus abscissus (Browne, 1974) comb. nov., Debus amplexicauda (Hagedorn, 1910) comb. nov., Debus armillatus (Schedl, 1933) comb. nov., Debus balbalanus (Eggers 1927) comb. nov., Debus blandus (Schedl, 1954) comb. nov., Debus cavatus (Browne, 1980) comb. nov., Debus cylindromorphus (Eggers, 1927) comb. nov., Debus dentatus (Blandford, 1895) comb. nov., Debus excavus (Schedl, 1964) comb. nov., Debus fischeri (Hagedorn, 1908) comb. nov., Debus hatanakai (Browne, 1983) comb. nov., Debus insitivus (Schedl, 1959) comb. nov., Debus persimilis (Eggers, 1927) comb. nov., Debus subdentatus (Browne, 1974) comb. nov., Debus trispinatus (Browne, 1981) comb. nov., Diuncus taxicornis (Schedl, 1971) comb. nov., Euwallacea agathis (Browne, 1984) comb. nov., Euwallacea assimilis (Eggers, 1927) comb. nov., Euwallacea bryanti (Sampson, 1919) comb. nov., Euwallacea latecarinatus (Schedl, 1936) comb. nov., Euwallacea pseudorudis (Schedl, 1951) comb. nov., Euwallacea semipolitus (Schedl, 1951) comb. nov., Euwallacea temetiuicus (Beeson, 1935) comb. nov., Immanus duploarmatus (Browne, 1962) comb. nov., Leptoxyleborus sublinearis (Eggers, 1940) comb. nov., Peridryocoetes pinguis (Browne, 1983) (Dryocoetini) comb. nov., Stictodex halli (Schedl, 1954) comb. nov., Stictodex rimulosus (Schedl, 1959) comb. nov., Terminalinus granurum (Browne, 1980) comb. nov., Terminalinus indonesianus (Browne, 1984) comb. nov., Terminalinus moluccanus (Browne, 1985) comb. nov., Terminalinus pseudomajor (Schedl, 1951) comb. nov., Terminalinus sublongus (Eggers, 1927) comb. nov., Terminalinus takeharai (Browne) comb. nov., Terminalinus xanthophyllus (Schedl, 1942) comb. res., Tricosa abberrans (Schedl, 1959) comb. nov., Xenoxylebora truncatula (Schedl, 1957) comb. nov., Xyleborinus figuratus (Schedl, 1959) comb. nov., Xylosandrus cancellatus (Eggers, 1936) comb. nov., all from Xyleborus. Fifteen new synonyms are proposed: Anisandrus ursulus (Eggers, 1923)(= Xyleborus lativentris Schedl, 1942 syn. nov.); Cyclorhipidion amanicus (Hagedorn, 1910)(= Xyleborus jongaensis Schedl, 1941 syn. nov.); Cyclorhipidion bodoanum (Reitter, 1913) (= Xyleborus takinoyensis Murayama, 1953 syn. nov.); Cyclorhipidion pelliculosum (Eichhoff, 1878) (= Xyleborus okinosenensis Murayama, 1961 syn. nov.); Cyclorhipidion repositum (Schedl, 1942) (= Xyleborus pruinosulus Browne, 1979 syn. nov.); Debus persimilis (Eggers, 1927) (= Xyleborus subdolosus Schedl, 1942c syn. nov.); Debus robustipennis (Schedl, 1954) (= Xyleborus interponens Schedl, 1954 syn. nov.); Euwallacea destruens (Blandford, 1896) (= Xyleborus procerior Schedl, 1942 syn. nov.); Euwallacea nigrosetosus (Schedl, 1939) (= Xyleborus nigripennis Schedl, 1951 syn. nov.); Euwallacea siporanus (Hagedorn, 1910) (= Xyleborus perakensis Schedl, 1942 syn. nov.); Microperus quercicola (Eggers, 1926) (= Xyleborus semistriatus Schedl, 1971 syn. nov.); Stictodex dimidiatus (Eggers, 1927) (= Xyleborus spicatus Browne, 1986 syn. nov.); Stictodex halli (Schedl, 1954) (= Xyleborus cuspidus Schedl, 1975 syn. nov.); Terminalinus Hopkins, 1915 (= Fortiborus Hulcr & Cognato 2010 syn. nov.); Terminalinus moluccanus (Browne, 1985) (= Xyleborus teminabani Browne, 1986 syn. nov.).